Adapting Chess Game into Physical Activity in Teaching Speaking for EFL Learners - Nurbani, Armelia Nungki (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2020)
Study of language games has widely spread based on the teachers’ experience in facing students’ difficulties in speaking English. Colorless speaking activities, fear of making mistakes, and inadequate of mastering vocabularies are some of the causes. Be a creative and innovative teacher is needed to encourage the students to be more active, confident, and enjoy in the class. Game is believed as one of shortcut that used by the teachers which can attract students’ attention. Well-chosen game is invaluable to help the teacher in speaking class. This study aims to describe the steps and the implementation of adapted game. Also, investigate the students’ perception of adapted game in the EFL speaking classroom. This single descriptive case study was conducted at one of English private courses in Sidoarjo where eighteen Senior High School students in Intermediate level participated as subjects. Interview and class observation were done to eighteen Intermediate students to know their responses regarding to the new adapted game. The finding demonstrated that chess-like game has a great potential to encourage the students’ willingness to speak. The students started to talk, feel relax and provoke a lot likewise all along speaking class had alive atmosphere. This study is not only able to illustrate the positive impacts of using adapted game but also add teacher references in adapting various kinds of passive game in their daily live to active game for speaking.